2021
DOI: 10.1146/annurev-micro-040921-050212
|View full text |Cite
|
Sign up to set email alerts
|

Expanding Archaeal Diversity and Phylogeny: Past, Present, and Future

Abstract: The discovery of the Archaea is a major scientific hallmark of the twentieth century. Since then, important features of their cell biology, physiology, ecology, and diversity have been revealed. Over the course of some 40 years, the diversity of known archaea has expanded from 2 to about 30 phyla comprising over 20,000 species. Most of this archaeal diversity has been revealed by environmental 16S rRNA amplicon sequencing surveys using a broad range of universal and targeted primers. Of the few primers that ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 134 publications
0
44
0
Order By: Relevance
“…Genome-resolved metagenomics has revolutionized our knowledge of archaeal diversity by giving us access to the genome of uncultured microorganisms at an unprecedented rate (Tahon et al ., 2021). In a recent metagenomic investigation of tundra soils in northern Finland (Pessi et al ., 2022, pre-print), we have manually binned and curated a MAG belonging to the genus “UBA10452”, an uncultured and largely uncharacterized lineage in the order Nitrososphaerales (“terrestrial group I.1b”) of the phylum Thaumarchaeota (Rinke et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Genome-resolved metagenomics has revolutionized our knowledge of archaeal diversity by giving us access to the genome of uncultured microorganisms at an unprecedented rate (Tahon et al ., 2021). In a recent metagenomic investigation of tundra soils in northern Finland (Pessi et al ., 2022, pre-print), we have manually binned and curated a MAG belonging to the genus “UBA10452”, an uncultured and largely uncharacterized lineage in the order Nitrososphaerales (“terrestrial group I.1b”) of the phylum Thaumarchaeota (Rinke et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Their study describes a core set of putative ribosome biogenesis factors widely conserved among archaea that may contribute to ribosome synthesis, although this is still to be proven experimentally. Notably, this study also reveals that the expansion of ribosome biogenesis factors characteristic of the eukaryotic pathway is not present in the Asgard archaea phylum which has been proposed to be more closely related to eukaryotes (Tahon et al, 2021). Altogether, this comprehensive study provides an important resource that will further help to functionally explore the archaeal ribosome biogenesis pathway and its evolution.…”
mentioning
confidence: 75%
“…At the end of the 1970s, Carl Woese identified microorganisms that belong to a separate domain of life, the archaea (Fox et al, 1977 ; Albers et al, 2013 ). In the subsequent years, in-depth studies of the molecular and cellular biology of archaea, as well as of their physiology and environmental distribution, have revealed that archaea possess some very unique and distinctive biological traits (Albers et al, 2013 ; Tahon et al, 2021 ).…”
mentioning
confidence: 99%
“… Archaeal diversity and their current phylogenetic relationship. A simplified archaeal phylogenetic tree based on Tahon et al (2021) is depicted. Archaea are divided into the Euryarchaea phylum, and the TACK, DPANN, Asgard superphyla.…”
Section: Introduction: Ribosomes and The Discovery Of Archaeamentioning
confidence: 99%